2019 IEEE International Conference on Big Data (Big Data) 2019
DOI: 10.1109/bigdata47090.2019.9006369
|View full text |Cite
|
Sign up to set email alerts
|

Scheduling in the Presence of Data Intensive Compute Jobs

Abstract: We study the performance of non-adaptive scheduling policies in computing systems with multiple servers. Compute jobs are mostly regular, with modest service requirements. However, there are sporadic data intensive jobs, whose expected service time is much higher than that of the regular jobs. For this model, we are interested in the effect of scheduling policies on the average time a job spends in the system. To this end, we introduce two performance indicators in a simplified, onlyarrival system. We believe … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 8 publications
0
1
0
Order By: Relevance
“…2) Write requests: It has been shown that the random write latency in distributed storage systems, can be well modeled by shifted exponential distribution [4], [9], [10], [35], [36]. The shifted exponential distribution can be approximated to an exponential distribution when the constant shift is much smaller than the mean of the distribution.…”
Section: Execution Of Read/write Requestsmentioning
confidence: 99%
“…2) Write requests: It has been shown that the random write latency in distributed storage systems, can be well modeled by shifted exponential distribution [4], [9], [10], [35], [36]. The shifted exponential distribution can be approximated to an exponential distribution when the constant shift is much smaller than the mean of the distribution.…”
Section: Execution Of Read/write Requestsmentioning
confidence: 99%